Pengaruh Air Rendaman Kulit Batang Pepaya Terhadap Kematian Jentik Aedes Aegypti pada Tempat Penampungan Air di Kecamatan Curup Tengah - Rustam Aji (Poltekkes Kemenkes Padang, 2019)
The Aedes aegypti larva which is not monitored develops into an adult mosquito, causing Dengue Fever. Eradication using fogging, abate powder, has an effect on the environment. Researchers are looking for a safe and effective natural larvicidal solution using papaya plants. Papaya plants contain the enzyme papain substance, the effect of papain protease can kill the larva of Aedes aegypti. This study aims to determine the effect of water soaking papaya bark on the death of Aedes egypti larvae. Research location in Curup Tengah District. Quasi-experimental type, Chi-square analysis, calculating odds ratio, Chi-square test. Approximately (94.4%) there were 34 dead larvae, a small portion (5.5%) had 2 live larvae, from 36 larvae of Aedes aegypti in 50 ml of water soaking the papaya bark under 1 minute. Chi-square analysis results P value = 0.04 <α0.05, there is a significant effect of water soaking papaya bark on larvae death of Aedes aegypti. The value of p value = 0.043, has the influence of water soaking papaya bark, odds ratio = 4.10 times. It is expected that the community will play a role in eradicating the larva of Aedes aegypti, by making a marinade of papaya bark poured into a water reservoir Keywords: Papaya bark, larvae of Aedes aegypti